Hubungan Tingkat Pengetahuan Petani dengan Efektivitas Pelaksanaan Program Kartu Tani di Kabupaten Semarang - Jorgi, Ryan Satya; Gayatri, Siwi; Dalmiyatun, Tutik (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
This research was motivated by the policies of the Central Java provincial government in overcoming the problem of distributing subsidized fertilizers through the farm card program, which in the implementation still had problems, especially at the farmer level. The study aimed to describe the implementation of Farmer Card Program (Program Kartu Tani) and to analyse the relationship between knowledge level of farmers and the effectiveness of Farmer Card Program (Program Kartu Tani) in Semarang Regency. This research was conducted from February to May 2018. Survey method was used in this study. Multistage random sampling method was used for determining respondents. Data collection was done by interview using a questionnaire. Data analysis were descriptive analysis and Rank Spearman correlation analysis using SPSS. This research showed the level of farmers knowledge about Farmer Card Program (Program Kartu Tani) was in the category of knowless. The level of effectiveness about implementation of the Farmer Card Program (Program Kartu Tani) was in the effective category. While the implementation of Farmer Card Program (Program Kartu Tani) at farmer level was effective because of the role farmer group in implementing program assisted by extension agent and related government institution although there were still face some obstacles that need to be improved to increase effectivity of farmer card implementation. There was a strong and significant relationship between the knowledge level and effectiveness of the Farmer Card Program (Program Kartu Tani), with the coefficient number 0.568.